Efficacy of chlorhexidine in the prevention of alveolar osteitis after permanent tooth extraction. Systematic review and meta-analysis. - Heber Arbildo-Vega; Marialejandra Sime; Edward Infantes; Fredy Cruzado; Tania Castillo (Universidad de Concepción., 2019)
Background: Dental extraction is a routine task performed by dental surgeons. This procedure may sometimes cause associated postoperative complications such as: edema, pain, trismus and alveolar osteitis (AO). Objective: To evaluate the efficacy of chlorhexidine (CHX) in the prevention of alveolar osteitis after permanent tooth extraction, through a systematic review and meta-analysis. Materials and Methods: A literature search was carried out until December 2018 in the following biomedical databases: PubMed, Embase, SciELO, Science Direct, SIGLE, LILACS, Google Scholar and The Cochrane Central Register of Controlled Trials (CENTRAL). The selection criteria for the studies were: randomized clinical trials published in the 5 years prior to the realization of this study, which reported the use of CHX in the prevention of AO. The risk of study bias was analyzed through the Cochrane Manual for systematic reviews of interventions. Results: The search strategy resulted in a selection of 22 articles; 17 of these were used to perform the meta-analysis. All of them reported that CHX is effective in preventing AO. Conclusion: The literature reviewed suggests that the use of CHX is effective in AO prevention; however, more studies comparing the efficacy of chlorhexidine gel with chlorhexidine used as an irrigant or as mouthwash are necessary.